2020
DOI: 10.1088/1361-6463/abb848
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of absorbance behavior and peak shift of RONS in plasma-activated water by UV absorption spectroscopy: dependency on gas impurity, pulse polarity, and solution pH

Abstract: In this paper, we employ UV absorption spectroscopy to monitor the generation and permeation of reactive oxygen and nitrogen species (RONS) in plasma-activated water (PAW) to revealthe dynamic variation mechanism of RONS chemistry. Parameters including gas impurity, pulse polarity and solution pH value are varied to explore their effects on the absorbance behavior and peak shift of absorption spectra as well as the permeation distribution of RONS. Regarding the absorbance behavior, experimental results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…Amplex Red reagent reacts with liquid phase H 2 O 2 at a dose ratio of 1:1 under the catalysis of HRP to produce Resorufin with red fluorescence [42]. Liu et al [43] showed that the spatial and temporal color permeation distribution of H 2 O 2 in a cuvette in real time via the chemical fluorescent probes-Amplex ® Red reagent. The color shift occurs from yellow to blue after 3 min of PAW treatment with different working gases or with acid, neutral, and alkaline solutions, and it distributes over the entire cuvette with the extension of time.…”
Section: Analysis Of Non-radicalsmentioning
confidence: 99%
“…Amplex Red reagent reacts with liquid phase H 2 O 2 at a dose ratio of 1:1 under the catalysis of HRP to produce Resorufin with red fluorescence [42]. Liu et al [43] showed that the spatial and temporal color permeation distribution of H 2 O 2 in a cuvette in real time via the chemical fluorescent probes-Amplex ® Red reagent. The color shift occurs from yellow to blue after 3 min of PAW treatment with different working gases or with acid, neutral, and alkaline solutions, and it distributes over the entire cuvette with the extension of time.…”
Section: Analysis Of Non-radicalsmentioning
confidence: 99%
“…In order to determine the composition of the main products produced by DBD air plasma, the products are analyzed by optical emission spectroscopy (OES), in which different emission spectral lines reflect the types of active particles in the excited state . As shown in Figure d, the spectrum in the range of 200–800 nm is detected and recorded.…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the composition of the main products produced by DBD air plasma, the products are analyzed by optical emission spectroscopy (OES), in which different emission spectral lines reflect the types of active particles in the excited state. 32 As shown in Figure 4d, the spectrum in the range of 200−800 nm is detected and recorded. The dominant components of the spectrum were identified as the N 2 (C 3 ∏ U → B 3 ∏ g ) second positive system (SPS), the weak band of N 2 (B 3 ∏ g → A 3 ∑ u ) first positive system (FPS), and the N 2 + (B 2 ∑ U + → X 2 ∏ g + ) first negative system (FNS).…”
Section: Nitrogen Fixation Effect Of the Dbd Plasmamentioning
confidence: 97%
“…NTAPP is an eco-friendly technology generated by an ionized gas that produces reactive species from the gas phase of plasma, plasma–air interaction, or interaction with treated/activated substrates [ 2 ]. Reactive species are of great scientific interest due to the action of their active constituents in areas such as, medicine, dentistry, agriculture, environment, and food [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The physicochemical reactions generated in plasma interaction with air create reactive species of oxygen and nitrogen (RONS), whose main constituents are nitrates (NO 3 ), nitrite (NO 2 ), peroxynitrite (ONOO − ), hydrogen peroxide (H 2 O 2 ), hydroxyl (OH), oxygen (O 2 ), superoxide (O 2 ), and ozone (O 3 ) [ 2 , 3 , 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive species are of great scientific interest due to the action of their active constituents in areas such as, medicine, dentistry, agriculture, environment, and food [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The physicochemical reactions generated in plasma interaction with air create reactive species of oxygen and nitrogen (RONS), whose main constituents are nitrates (NO 3 ), nitrite (NO 2 ), peroxynitrite (ONOO − ), hydrogen peroxide (H 2 O 2 ), hydroxyl (OH), oxygen (O 2 ), superoxide (O 2 ), and ozone (O 3 ) [ 2 , 3 , 5 , 10 ]. These plasmas are generally generated as plasma jets (PJ) and may be applied directly or indirectly [ 1 , 8 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%